AIDS activism and alliances - Aggleton, Peter; Davies, Peter; Hart, Graham (Social aspects of AIDS, 1997)
From the start of the AIDS epidemic there have been calls for greater solidarity between affected groups and communities, and public health services. This can be seen both in the move towards healthy alliances in health service work, and in the demands of AIDS activists worldwide. This text brings together specially selected papers addressing these and related themes given at the Eighth Conference on Social Aspects of AIDS held in London in late 1995. Among the issues examined are profession and policy; the heightened vulnerability of groups such as women and younger gay men; and issues of drug use, disability and HIV prevention.